Electrochemical noise analysis on the pit corrosion susceptibility of biodegradable AZ31 magnesium alloy in four types of simulated body solutions. Issue 10 (October 2018) - Wang, Changgang; Wu, Liping; Xue, Fang; Ma, Rongyao; Etim, Ini-Ibehe Nabuk; Hao, Xuehui; Dong, Junhua; Ke, Wei
Abstract: Magnesium alloys have been investigated as biodegradable implant materials since the last century. Non-uniform degradation caused by local corrosion limits their application, and no appropriate technology has been used in the research. In this study, electrochemical noise has been used to study the pit corrosion on magnesium alloy AZ31 in four types of simulated body solutions, and the data have been analyzed using wavelet analysis and stochastic theory. Combining these with the conventional polarization curves, mass loss tests and scanning electron microscopy, the electrochemical noise results implied that AZ31 alloy in normal saline has the fastest corrosion rate, a high pit initiation rate, and maximum pit growth probability. In Hanks' balanced salt solution and phosphate-buffered saline, AZ31 alloy has a high pit initiation rate and larger pit growth probability, while in simulated body fluid, AZ31 alloy has the slowest corrosion rate, lowest pit initiation rate and smallest pit growth probability.